Molecular Spectroscopy of Nano- and Bio-Systems Using Quantum Chemistry - Foerster, Aleksandra (2023)
Computational molecular spectroscopy, as a sub-field of quantum chemistry, allows one to obtain a comprehensive picture of investigated molecules and systems in terms of their structure and properties. It not only helps in the interpretation and understanding of the experimental spectra or predicting spectroscopic properties of molecular systems but can also be a great tool in the development of new materials. Various theoretical and computational methods have been successfully applied to solve different problems in many branches of science, however applying them to the investigation of larger and more complex systems remains a challenge. This work focuses on using Density Functional Theory (DFT) and Time-Dependent Density Functional Theory (TDDFT) methods to investigate the quantum chemical and spectroscopic properties of larger-sized systems. Four different types of molecules were studied, quantum dot (QD) clusters, endohedral fullerenes with an encapsulated metal atom, endohedral fullerenes with diatomic molecules, and the secondary structures of proteins. Methods to accurately and efficiently simulate X-ray and UV-Vis spectroscopy to reproduce experimental data and provide insights into the underlying chemical and physical processes associated with these techniques and the systems studied are provided.